Development and proliferation of feline endometrial glands from fetal life to ovarian cyclicity - López Merlo, Mariana Lucía (2017)
In this study it was determined the progression of uterine gland development from late gestation to puberty in domestic felids. Cell proliferation patterns for luminal (LE), glandular epithelium (GE) as well as stroma (S) were also described. Twenty-four uteri from female kittens: 45 and 65 days of gestation and 1 to 5, 8, 12, 16, 20 and 24 weeks postnatally were obtained. Uterine cross-sections were submitted for routine histological and immunohistochemical quantification of proliferating cell nuclear antigen (PCNA) techniques. Although prenatal uteri presented no indication of adenogenesis, 1 week old uteri revealed an incipient budding of the LE. During the second week budding increased and a mild degree of tubulogenesis of the GE into the stroma was detected. From the third to fifth weeks coiling, branching and cross-sections of glands appeared. These latter findings were more evident in week 8 when GE began to penetrate through much of the S to week 24. PCNA immunostaining revealed that DNA synthesis decreased throughout the study in the 3 cell compartments; (P < 0.01). Luminal proliferation began prenatally, it maintained up to postnatal week 8 to markedly decrease to puberty (P < 0.01). From postnatal week 3 up to week 8, GE mitotic activity was elevated becoming low thereafter (P < 0.01). Stroma actively proliferated prenatally (P < 0.01), diminishing up to week 8 (P < 0.01) and again during the last weeks (P < 0.01) of the study. It was concluded that, in domestic felids, proliferation of LE begins prenatally, histological uterine adenogenesis commenced during the first postnatal week and both events concluded by postnatal weeks 5–8.